The effects of text length on the readability of model essays - Baker, John R. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Providing self-access libraries and the texts therein (anthologies of model essays) has long been cited as an essential part of university writing center services, as the reading of model essays has been found to positively affect the reading-writing relationship. When choosing such texts, readability is typically measured via quantitative readability formulae (e.g., the Lexile Readability Formula). However, this practice only measures two (i.e., semantic, syntactic) of the many features that influence readability, leaving others (e.g., text length) unexplored. To address this, this article reports the findings of an exploratory mixed-methods study conducted in an Asian university writing center setting which showed that the informants' ranking of ease and difficulty was significantly different than the Lexile Formula and that text length had a significant positive association with this ranking. It was further found that length was viewed as (a) a primary (i.e., an isolated feature), (b) a conjoined feature (i.e., comprising two or more associated entities where the second impacts the first: interest, vocabulary), and (c) a feature which impacts the influences of other features (interest, vocabulary, and vocabulary in context). The study also offers suggestions for writing studies professionals (teachers, writing center staff) and the publishing industry that text length be included in a hybrid (quantitative-qualitative) procedure when considering the difficulty of model essays found in anthologies.